Role of Immunohistochemistry in the Diagnosis of Leptospirosis in Neotropical Primates - Grumann, Marta Regina; da Silva, Zigomar; Luz, Flávia Serena da; Filho, José Roberta Silva; Machado, Tanise Policarpo; Costa, Marcio Machado; Vieira, Maria Isabel Botelho; Motta, Adriana Costa da (Acta Scientiae Veterinariae, 2017)
Background: Leptospirosis is considered the most widespread zoonosis worldwide, occurring more frequently in tropical and developing regions. The aim of the present study was to detect the presence of Leptospira spp. in different primate tissues, using immunohistochemical (IHC) assays, taking advantage of the considerable number of necropsies compatible with a diagnosis of leptospirosis in neotropical primates at the Animal Pathology Laboratory (APL) of the University of Passo Fundo (UPF) in the northern region of Rio Grande do Sul. Materials, Methods & Results: Paraffin-embedded primate tissue samples were selected from necropsy examinations and subjected to IHC. The streptavidin-biotin-peroxidase method was used with diaminobenzidine chromogen (DAB) to verify immunostaining. Of the101 primates tested for Leptospira spp., 51.48% were positive; taining was distributed between lung (76.92%), liver (44.23%), and kidney (32.69%) tissue. Analysis of the combined anatomopathological verification data of the studied organs revealed a high frequency of lesions commonly observed in the tissues of animals exposed to the pathogen. For complementary diagnosis, an anti-Leptospira spp. antibody test was performed in primates at the UPF-Zoo, from which a population of the necropsied animals originated. The microscopic agglutination test (MAT) was utilized, which demonstrated 90.47% positivity in 21 individuals; sejroe and panama were the most frequent serovars. Discussion: Different intensities of tissue immunostaining were observed. Areas of fragmented or diffuse staining were considered to indicate equal positivity to that indicated by areas of staining with preserved morphology. Of 52 Leptospirapositive primates, most presented some degree of staining in lung samples, which shows a high level of involvement for this organ in primate leptospirosis. Conventional pathological diagnostic methods do not allow fort issue antigen recognition, thus making the IHC technique important to facilitate conclusive antigen sample verification. In the liver, leptospires were detected mostly between the sinusoids, hepatocytes, and Kupffer cells. In kidney tissues, staining indicated small agglomerates in the tubular lumen, interstitium, and glomeruli. All these forms of presentation have been previously reported. Considering that we detected the highest number of positive samples in lung tissue, followed by those from liver and kidney tissue, we argue that the IHC technique, when applied to samples of these three tissues, decreases the chance of false negatives. Anatomopathological studies of primate leptospirosis are scarce. In dogs, renal lesions are characterized by the necrosis and degeneration of tubular epithelium, cellular debris, and hyaline cylinders. In the liver, hepatocyte cord dissociation and biliary pigment accumulation within the canaliculi and hepatocellular necrosis are observed. These findings are similar to those from our study. In the lung, diffuse alveolar lesions are reported, with hemorrhage and edema, in addition to capillaritis. The high frequency of Leptospira-positive animals determined by serological examination was consistent with the IHC findings, thus confirming the pathogen’s high prevalence in neotropical primate populations in the studied region. Serological surveys on primate populations have already been carried out and have revealed frequency and serovar variations between regions. Immunohistochemical examination allows the detection of leptospires in various tissues and should be used based on the characteristics of the investigated case.